STRATEGI KOMUNIKASI INTERNAL DALAM MEMBANGUN KETERLIBATAN KARYAWAN PADA PERUSAHAAN DI ERA DIGITAL - Edwin Yustian Nulhakim; Muhammad Reza Panangian; Exsan Adde (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2026)
Digital transformation introduces unprecedented complexity in organizational internal communication management, necessitating strategic reconfiguration to sustain employee engagement. This qualitative research employing case study design explores digital-based internal communication strategies in cultivating employee engagement within contemporary organizational contexts. Data collection was executed through semi-structured in-depth interviews, non-participant observation, and organizational document analysis with purposively selected participants. Thematic analysis identified digital communication platform transformation, communication transparency as engagement foundation, transformative leadership roles, and implementation challenges as principal themes. Findings delineate that information transparency, leadership responsiveness, and appropriate communication technology integration contribute significantly toward employee engagement enhancement. Barriers encompass information overload, digital competency disparities, and diminished socio-emotional nuances in virtual interactions. Practical implications emphasize integrated omnichannel approach adoption, sustained digital literacy investments, and virtual social interaction mechanism creation to optimize internal communication ecosystems. This research contributes theoretically to organizational communication body of knowledge and provides practical recommendations for practitioners in designing adaptive communication strategies responsive to digital era dynamics.